2020
DOI: 10.1111/jch.13929
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension burden and challenges across the hypertension treatment cascade among adults enrolled in HIV care in northern Tanzania

Abstract: Failure to address hypertension among people living with HIV (PLWH) may undermine the significant progress made toward reducing mortality among this high‐risk population in sub‐Saharan Africa (SSA). Here, the authors report hypertension prevalence, diagnosis, and treatment among patients enrolled in HIV care in Tanzania. Patients attending an HIV clinic were consecutively screened for hypertension. Hypertension was defined as follows: a single blood pressure measurement ≥160 mm Hg systolic or ≥100 mm Hg diasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…9 However, a recent study in northern Tanzania examining a cohort of hypertensive patients enrolled in HIV care revealed that more than half of all participants had never had a previous blood pressure measurement, two-thirds were unaware of their diagnosis, 90% were not on antihypertensive treatment, and none had controlled blood pressure suggesting a discordance between real-world practice and treatment guidelines. 10 Challenges across the hypertension continuum of care among PWH in SSA are likely multifactorial. [11][12][13] A qualitative study examining perspectives of hypertension care among hypertensive patients receiving HIV treatment in northern Tanzania identified poor patient knowledge as a predominant barrier to hypertension care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, a recent study in northern Tanzania examining a cohort of hypertensive patients enrolled in HIV care revealed that more than half of all participants had never had a previous blood pressure measurement, two-thirds were unaware of their diagnosis, 90% were not on antihypertensive treatment, and none had controlled blood pressure suggesting a discordance between real-world practice and treatment guidelines. 10 Challenges across the hypertension continuum of care among PWH in SSA are likely multifactorial. [11][12][13] A qualitative study examining perspectives of hypertension care among hypertensive patients receiving HIV treatment in northern Tanzania identified poor patient knowledge as a predominant barrier to hypertension care.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, a recent study in northern Tanzania examining a cohort of hypertensive patients enrolled in HIV care revealed that more than half of all participants had never had a previous blood pressure measurement, two-thirds were unaware of their diagnosis, 90% were not on antihypertensive treatment, and none had controlled blood pressure suggesting a discordance between real-world practice and treatment guidelines. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Despite this increased burden of disease, most patients with hypertension in SSA are not on treatment [ 10 ]. These concerning trends are also present among PLHIV [ 11 ]: a recent study in northern Tanzania found that among a cohort of hypertensive patients enrolled in HIV care, 65% were unaware of their diagnosis, 90% were not on antihypertensive treatment and all had uncontrolled blood pressure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with both HIV and IHD have trouble navigating siloed care systems for their HIV and cardiovascular needs in SSA. PLWH are rarely screened for cardiovascular risk factors such as hypertension during HIV follow-up visits, experience delays in IHD risk factor diagnosis, do not receive referrals or linkages to cardiovascular care, and rarely speak to a single provider about co-occurring conditions [7,8]. These barriers, combined with financial and social barriers to adequate care, lead to poor understanding of cardiovascular risks and lower adherence to cardiovascular medications in PLWH in SSA [7][8][9][10][11].…”
mentioning
confidence: 99%
“…PLWH are rarely screened for cardiovascular risk factors such as hypertension during HIV follow-up visits, experience delays in IHD risk factor diagnosis, do not receive referrals or linkages to cardiovascular care, and rarely speak to a single provider about co-occurring conditions [7,8]. These barriers, combined with financial and social barriers to adequate care, lead to poor understanding of cardiovascular risks and lower adherence to cardiovascular medications in PLWH in SSA [7][8][9][10][11]. Understanding barriers to IHD prevention and care is critical to improving IHD morbidity and mortality among HIV-infected patients.…”
mentioning
confidence: 99%